Pengembangan model course review horay berbantu media pasutar (papan surat bangun datar) untuk meningkatkan hasil belajar matematika kelas III SD - Etha Fauziyyatul Amiiroh; Sri Utaminingsih; Mochamad Widjanarko (COLLASE (Creative of Learning Students Elementary Education), 2023)
This study aims to describe the CRH model assisted by the medium of social media on the mathematics learning outcomes of third grade elementary school students and to describe the CRH model assisted by the media learning outcomes of third grade elementary school students. This type of research is development research or commonly known as Research and Development (RnD). The development model used in this research is the development model according to Borg & Gall. The population of this study were third grade students in the Sultan Agung Medini Cluster, Undaan, Kudus. The samples taken were third grade students at SD 1 Medini Undaan Kudus with a total of 20 students.The search results are used on the aspect of display and use of media, the media design expert used states that 80% and is very feasible to use. In the aspect of display and use of media, mathematical media experts stated that the product was very feasible to use with a score of 95%. Aspects of assessment by education practitioners scored 98% with product categories that were very suitable for use. Based on the results of product trials and product trials, the results showed satisfactory results. The posttest score was 11.25 higher than the pretest score. This study uses data analysis techniques using the T test. Normality test and homogeneity test were carried out to determine the CRH model assisted by tide media. The normality test was tested using the posttest value data obtained by L0 of 0.1380 and Ltable of 0.190 so that the hypothesis can be accepted or the data comes from a normally distributed population. While the pretest value obtained L0 0.1257 and L table 0.190 so that the hypothesis can be accepted or the data comes from a population that is normally distributed. The homogeneity test results from the results of the pretest and posttest values based on the calculation results obtained Fcount of 1.8785 with Ftable of 2.1683. Because Fcount < Ftable, the hypothesis can be accepted or the data comes from a homogeneous population. After testing the data analysis, then the t-test was carried out, in the t-test obtained tcount = 2.4117. Then the price of tcount is compared with ttable. Ttable is determined by dk= n1+n2 – 2 = 38 and level = 0.05 is 2.0227. Based on the test criteria that H0 is accepted if tcount is less than or equal to ttable. It turns out that the value of tcount is greater than ttable which is 2.4117>2.0227, so it can be said that H0 is rejected and accepted, which means that the development of the media-assisted CRH learning model is effective on student learning outcomes and mastery learning.